2019
DOI: 10.5606/tgkdc.dergisi.2019.16879
|View full text |Cite
|
Sign up to set email alerts
|

Early and mid-term results of frozen elephant trunk procedure for acute type A aortic dissection

Abstract: Bu çalışmada akut tip A aort diseksiyonlu hastalarda rezidüel sahte lümeni çıkarmak ve geç dönem komplikasyonları önlemek için kullandığımız E-vita OPEN PLUS stent grefti ile total torasik aort onarımının erken ve orta dönem sonuçları araştırıldı.Ça lış ma pla nı: Çalışmaya Kasım 2013 -Kasım 2017 tarihleri arasında akut tip A aort diseksiyonu nedeniyle frozen elephant trunk stent grefti ile total torasik aort onarımı geçiren 41 hasta (29 erkek, 12 kadın; ort. yaş 51.9±10.4 yıl; dağılım, 30-77 yıl) dahil edildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…In agreement with our study, a work done in Turkey by Akbulut et al reported that 93.9% and 54.4% of patients had thrombosed false aortic lumen at pulmonary and diaphragmatic levels, respectively, after one month of frozen elephant trunk implantation [ 9 ]. Kuroda et al reported a significant shrinkage of the false aortic lumen in the frozen elephant trunk segment, but did not find significant change in the false lumen in descending aorta, diaphragmatic hiatus and renal artery segments as the false lumen remained stable [ 10 ] Ouzounian et al reported a significant reduction in the diameter of the false aortic lumen following frozen elephant trunk surgery up to one-year follow-up of patients [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our study, a work done in Turkey by Akbulut et al reported that 93.9% and 54.4% of patients had thrombosed false aortic lumen at pulmonary and diaphragmatic levels, respectively, after one month of frozen elephant trunk implantation [ 9 ]. Kuroda et al reported a significant shrinkage of the false aortic lumen in the frozen elephant trunk segment, but did not find significant change in the false lumen in descending aorta, diaphragmatic hiatus and renal artery segments as the false lumen remained stable [ 10 ] Ouzounian et al reported a significant reduction in the diameter of the false aortic lumen following frozen elephant trunk surgery up to one-year follow-up of patients [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…After reviewing shreds of evidence, a total of 35 studies including 3211 patients were entered into the quantitative analysis (Figure 1). 11–44 The median size of reviewed reports was 72 patients (interquartile range 38 – 122). The majority of studies were performed in Chinese institutions, 19 studies including 2026 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Of 64 studies reporting outcomes of patients included in this report 13–76 . The proportions of studies from Asia, Europe, and North America were 54.7%, 31.3%, and 10.9%, respectively.…”
Section: Methodsmentioning
confidence: 99%